Single-cell RNA sequencing identifies a novel proliferation cell type affecting clinical outcome of pancreatic ductal adenocarcinoma - Ye, Bicheng; Wang, Qi; Zhu, Xiaofeng; Zeng, Lingling; Luo, Huiyuan; Xiong, Yan; Li, Qin; Zhu, Qinmei; Zhao, Songyun; Chen, Ting; Xie, Jingen (Frontiers in Oncology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is an extremely deadly neoplasm, with only a 5-year survival rate of around 9%. The tumor and its microenvironment are highly heterogeneous, and it is still unknown which cell types influence patient outcomes. In this study, we have identified a novel cell type with high proliferative capacity, named Prol, which is enriched with genes related to cell cycle and mitosis.Using bulk RNA sequencing (RNA-seq), we observed that the proportion of Prol cells was significantly increased in PDAC, and Prol cells were associated with reduced overall survival (OS) and progression-free survival (PFS). Additionally, the marker genes of Prol cell type, identified from single-cell RNA sequencing (scRNA-seq) data, were upregulated and associated with poor prognosis in the bulk RNA sequencing (bulk RNA-seq) data. We further confirmed that mutant KRAS and TP53 resulted in an increased abundance of Prol cells and that these cells were associated with an immunosuppressive and cold tumor microenvironment in PDAC. Spatial Transcriptome determined the spatial location of Prol cells. Additionally, patients with a lower proportion of Prol cells in PDAC may benefit more from immunotherapy and gemcitabine treatment. Furthermore, we employed unbiased machine learning integration algorithms to develop a Prol signature that can precisely quantify the abundance of Prol cells and accurately predict prognosis. Lastly, we verified the differential expression of the Prol signature gene LY6D using immunohistochemistry and qRT-PCR. In summary, by integrating bulk RNA-seq and scRNA-seq, we identified a novel proliferative cell type, Prol, which influences the OS and PFS of 3 PDAC patients. Our study enhances our understanding of the novel cell type in PDAC and its potential clinical implications.